Oceanology: Implications for the Field of Education in the Maritime World - Syahriati Syahriati (Postgraduate, University of Mataram, 2024)
This article discusses the importance of education in the maritime industry, particularly its implications for maritime education. This research adopts a comprehensive mixed methodology to analyze the influence of language in marine education and maritime industry practices at large. The methodology includes three main components: surveys, in-depth interviews, and document analysis, providing a holistic view of language dynamics in the maritime sector. This article highlights the challenges in marine education concerning language teaching and proposes the integration of language learning into the curriculum. The aim is to increase the effectiveness of maritime education and ensure more excellent safety at sea. With a focus on developing language learning strategies, this article proposes approaches to address the linguistic skills gap among seafarers, support maritime safety, and strengthen international cooperation in the marine industry.